Oxygen enhanced lung MRI by simultaneous measurement of T1 and T2* during free breathing using ultrashort TE - Triphan, Simon M. F.; Kauczor, Hans-Ulrich (Journal of magnetic resonance imaging, 2015)
Purpose: to provide a robust method for the simultaneous quantification of T1 and T2* in the human lung during free breathing. Breathing pure oxygen accelerates T1 and T2* relaxation in the lung. While T1 shortening reflects an increased amount of dissolved molecular oxygen in lung tissue, T2* shortening shows an increased concentration of oxygen in the alveolar gas. Therefore, both parameters reflect different aspects of the oxygen uptake and provide complementary lung functional information.Materials and Methods: a segmented inversion recovery Look-Locker multiecho sequence based on a multiecho 2D ultrashort TE (UTE) was employed for simultaneous T1 and T2* quantification. The radial projections follow a modified golden angle ordering, allowing for respiratory self-gating and thus the reconstruction of a series of differently T1 and T2*-weighted images in arbitrary breathing states. The method was evaluated in nine healthy volunteers while breathing room air and pure oxygen, with two volunteers examined at five oxygen concentrations. Results: relative differences of ΔT1 between 7.9% and 12.7% and of ΔT2* between 13.2% and 6.0% were found. Conclusion: the proposed method provides inherently coregistered, quantitative T1 and T2* maps in both expiration and inspiration from a single measurement acquired during free breathing and is thus well suited for clinical application.J. Magn. Reson. Imaging 2015;41:1708-1714. © 2014 Wiley Periodicals, Inc.